Determinants of alcohol consumption among adolescents: is mindfulness a predictor factor? - Arıcı Gürbüz, Asiye; Akdağ, Berhan (Journal of Dependence, 2025)
Objective: While the relationship between mindfulness and alcohol consumption is well-documented in adults, it remains underexplored in adolescent populations. This study aimed to examine the predictive role of mindfulness in alcohol consumption among adolescents. Method: The study included a cohort of adolescents (n = 70) receiving care at a child and adolescent psychiatry outpatient clinic who reported alcohol use. Participants completed a series of validated measures during face-to-face interviews, including the Child and Adolescent Mindfulness Measure (CAMM), the Kessler–10 Psychological Distress Scale (K10), the Drinking Motives Questionnaire–Revised–Coping Motives (DMQ–R–CM), and the Alcohol Use Disorders Identification Test–Consumption (AUDIT–C). Results: The mean participant age was 16.99 years, with 54.3% being male. Female gender was a significant negative predictor of DMQ–R–CM scores (B = –3.936, p = .022), whereas higher K10 scores were positively associated with DMQ–R–CM scores (B = .280, p = .002). Additionally, both the duration of alcohol use (B = .861, p <.001) and K10 scores were significant positive predictors of AUDIT–C scores (B = .066, p =.021). In contrast, higher CAMM scores were negatively associated with AUDIT–C scores (B = –.079, p = .029). Conclusion: The findings indicate the potential role of mindfulness in mitigating alcohol consumption among adolescents. Furthermore, the results underscore the necessity of implementing policies that promote mental health and prevent the initiation of alcohol consumption in this population.